Analysis of the Development of Bali Cattle Population in Agriculture Ecosystem of Timor Island using System Dynamics - Fuah, Asnath Maria; Yani, Ahmad; Priyanto, Rudy; Purwanto, Bagus Priyo; Riwukore, Jefirstson Richset; Habaora, Fellyanus (ANIMAL PRODUCTION, 2020)
Developing Bali cattle population in Timor Island, East Nusa Tenggara province carries a potential issue regarding cattle population. The objective of this research was to conduct an analysis and projection of the development of Bali cattle population in the agricultural ecosystem in Timor Island using system dynamics. The research was conducted from January to September 2018. The research location was determined purposively based on the characteristics of the agricultural ecosystem located in Kupang Regency and Kupang City. The research used 60 Bali cattle and involved 102 rancher respondents. Interviews and field observations were conducted to obtain primary and secondary data. Data analysis was done by building a system dynamics using Powersim and interpreting the simulation results for the next 30 years. The analysis results of the system dynamics showed that a declining population of Bali cattle over the next 19 or 25 years due to the ranchers' current behavior. The contributing factors included calf mortality that reached 29.6% per year; Bali cow mortality was up to 14.1% per year; calving interval was 22 months; traditional farm management that it is not economical; and the rate of livestock export reached 29.5% per year of the total population. Rancher management interventions and farm policies to reduce the inhibiting factors of cattle productivity are needed to maintain the population of Bali cattle in Timor Island, especially in the agricultural ecosystem.